The Effect of Antenatal Education Based on a Mobile Application in Regional Languages ​​on Pregnant Women's Self-Efficacy in Preventing Preeclampsia in Coastal Areas of Southeast Sulawesi - Andriyani (CV. Q2 Lantera Ilmiah Institut, 2025)
Preeclampsia is a major pregnancy complication contributing to high maternal morbidity and mortality, particularly in coastal areas with limited access to health services. Low maternal self-efficacy plays a critical role in delayed prevention and early detection of preeclampsia. This study aimed to analyze the effect of antenatal education delivered through a local-language mobile application on pregnant women’s self-efficacy in preventing preeclampsia in coastal areas of Southeast Sulawesi. A quasi-experimental pre-test/post-test design with a control group was applied. A total of 150 second-trimester pregnant women at moderate risk of preeclampsia were assigned to an intervention group (n=75) and a control group (n=75). The intervention group received 8 weeks of antenatal education via a local-language mobile application featuring interactive learning modules, audio narration, and reminder notifications, while the control group received conventional education from village midwives. Self-efficacy was measured using the 12-item Bandura scale. Data were analyzed using t-tests, Mann–Whitney tests, and effect size calculations. The intervention group showed a significant increase in self-efficacy from 42.3±6.1 to 58.7±5.4 (Δ=+16.4; p<0.001), which was substantially higher than the control group (Δ=+5.4; p=0.012). The between-group difference was highly significant (p<0.001) with a large effect size (η²=0.42). Increased self-efficacy was accompanied by improved preventive behaviors and a reduced incidence of third-trimester preeclampsia. Local-language mobile application–based antenatal education is effective in improving pregnant women’s self-efficacy for preeclampsia prevention in coastal settings. This culturally adaptive digital intervention represents a promising promotive–preventive strategy for regions with limited health service access.